2016
DOI: 10.1039/c6ra13409b
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic profiles and the in vivo antioxidant effect of nipa vinegar on paracetamol induced liver damage

Abstract: Nipa vinegar, which is rich in gallic acid and protocatechuic acid, has reverted the paracetamol-induced liver damage in mice by reduction of inflammation and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The standard deviation was calculated using one-way analysis of variance (ANOVA) and Duncan's multiple range tests. Table 3 summarises the in vitro antioxidant activities and the soluble phenolic acid derivatives identified in coconut juice vinegar and compares the data to the literature data for vinegars prepared from nipah 19 and pineapple 20 juices. According to the results, pineapple juice vinegar exhibited the highest TPC, FRAP values and radical scavenging activities compared to the coconut and nipah juice vinegars.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The standard deviation was calculated using one-way analysis of variance (ANOVA) and Duncan's multiple range tests. Table 3 summarises the in vitro antioxidant activities and the soluble phenolic acid derivatives identified in coconut juice vinegar and compares the data to the literature data for vinegars prepared from nipah 19 and pineapple 20 juices. According to the results, pineapple juice vinegar exhibited the highest TPC, FRAP values and radical scavenging activities compared to the coconut and nipah juice vinegars.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Considering that vinegar can be produced from different sources and via distinct processes, the antioxidant strength may vary among vinegars, due to the differences in minerals, vitamins and phenolic acid content of the original source. 32,33 Table 3 compares the differences in the antioxidative activities of coconut juice vinegar with the literature data for nipah 19 and pineapple 20 juice vinegars, produced using the same fermentation method. Among these vinegars, pineapple juice vinegar contained the highest diversity and concentration of soluble phenolic acids, which may contribute to its highest level of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that soy isoflavones reduced hepatotoxicity caused by APAP via suppressing cytochrome P450‐mediated bioactivation and GSH depletion, and accelerating drug excretion in urine (Liu et al., ). As for spices and other seasonings, it was shown that pineapple ( Ananas comosus ) vinegar and nipa ( Nypa fruticans ) vinegar could similarly decrease serum biomarkers, normalize hepatic antioxidant levels, and inhibit the expression of inflammatory factor and cytochrome P450 (Beh et al., ; Mohamad et al., ).…”
Section: Protective Effects Of Natural Products On Drug‐induced Livermentioning
confidence: 99%